The Effect of Cardiopulmonary Resuscitation (CPR) Skills Training in Emergency Management: Case Study in a General Hospital - Ardenny, Ardenny; Jie, Lie; Jonathan, Bouyea; Intes, Amina (Journal of World Future Medicine, Health and Nursing, 2024)
Cardiopulmonary resuscitation (CPR) skills are a crucial aspect of handling medical emergencies, especially in a general hospital environment. In this context, CPR training is important to increase the competency of medical personnel in responding to emergencies involving cardiac or respiratory arrest. However, the direct impact of CPR training on the performance of medical practitioners in emergency management still requires more in-depth research. This study aimed to evaluate the effect of CPR skills training on emergency management in public hospitals. The primary focus is to determine whether CPR training improves medical practitioners’ readiness and performance in responding to emergencies, as well as whether it helps in increasing patient survival rates. This research method uses a case study approach in a particular public hospital. The results showed that CPR skills training significantly improved the performance of medical practitioners in handling emergencies in public hospitals. The group that had undergone CPR training showed a faster and more effective response rate in providing emergency resuscitation measures. In addition, there is a significant increase in the survival rate of patients who receive treatment from medical practitioners who have been trained in CPR. This research concludes that CPR skills training has a significant positive impact on handling emergencies in public hospitals. The increased performance of medical practitioners in responding to emergencies and the increase in patient survival rates are strong evidence of the importance of CPR training in increasing the readiness and effectiveness of medical treatment in the hospital environment. Therefore, it is recommended that CPR training continue to be improved and routinely integrated into medical personnel training programs.